New records and distribution expansion for Neotropical water-striders (Insecta: Heteroptera: Gerromorpha) - Moreira, Felipe Ferraz Figueiredo; Ribeiro, José Ricardo Inácio; Nessimian, Jorge Luiz; Itoyama, Mary Massumi [UNESP]; Castanhole, Márcia Maria Urbanin [UNESP]; Pereira, Luis Lenin Vicente [UNESP] (My University, 2011)
Based on material from several collections, summarized distributions and new records are presented for selected Neotropical species of Gerromorpha of the families Gerridae (Brachymetra albinervis albinervis, B. furva, B. lata, B. shawi, Cylindrostethus erythropus, C. linearis, C. palmaris, C. regulus, Halobatopsis platensis, Limnogonus aduncus aduncus, L. hyalinus, L. ignotus, L. profugus, L. recurvus, Neogerris lubricus, N. magnus, N. lotus, N. visendus, Ovatametra gualeguay, Rheumatobates crassifemur crassifemur, R. c. esakii, Tachygerris adamsoni, T. celocis and T. surinamensis), Hydrometridae (Hydrometra guianana and H. sztolcmani) and Mesoveliidae (Mesovelia amoena, M. mulsanti and Mesoveloidea williamsi).